Enhancing catalytic CH4 oxidation over Co3O4/SiO2 core–shell catalyst by substituting Co2+ with Mn2+. Issue 1 (31st December 2020) - Wang, Haiwang; Li, Jinlong; Liu, Wenge; Xu, Xin; Wei, Xinfang; Chao, Li; Zhao, Ruifeng; Qi, Xiwei; Che, Ling
Abstract: Co3 O4, a transition metal oxide with spinel structure, has attracted wide attention due to its high catalytic activity in the field of catalytic oxidation of low concentration methane. However, due to the harsh conditions of methane catalytic reaction on catalysts, of which the high reaction temperature and complex reaction environment often lead to the deactivation and sintering of Co3 O4 catalyst, improving the comprehensive performance of Co3 O4 catalyst has become the current research hotspot and urgent demand. Core-shell flower-spheroidal cobalt-manganese composite catalyst was prepared in this paper by hydrothermal method, which gave full play to the advantages of carrier, special morphology and doping modification, reduced the risk of sintering and deactivation of Co3 O4, and showed higher catalytic activity. Through SEM, EDS, and BET test and analysis, Mn1/Co/SiO2 has better microstructure and structure than Co3 O4 /SiO2 . For example, the dispersion of Mn1/Co/SiO2 and the uniform distribution of elements are higher, and the values of surface area and pore volume are larger (129.956 m 2 /g → 180.639 m 2 /g, 0.333363 cm 3 /g → 0.398030 cm 3 /g). Combined with XRD and XPS analysis, it is concluded that Mn 2+ manganese ion replaces Co 2+ and causes lattice distortion of Co3 O4, which promotes the production and mobility of reactive oxygen species, further increasing catalytic activity. Compared with Co3 O4 /SiO2, methane conversion at 350 °C and 450 °C increased by 10% and 6%, respectively. Graphical Abstract: uf0001